Emergence and evolution of heterocyte glycolipid biosynthesis enabled specialized nitrogen fixation in cyanobacteria - Ruth Pérez Gallego; F. A. Bastiaan von Meijenfeldt; Nicole J. Bale; Jaap S. Sinninghe Damsté; Laura Villanueva (Proceedings of the National Academy of Sciences, 2025)
Heterocytes, specialized cells for nitrogen fixation in cyanobacteria, are surrounded by heterocyte glycolipids (HGs), which contribute to protection of the nitrogenase enzyme from oxygen. Diverse HGs preserve in the sediment and have been widely used as evidence of past nitrogen fixation, and structural variation has been suggested to preserve taxonomic information and reflect paleoenvironmental conditions. Here, by comprehensive HG identification and screening of HG biosynthetic gene clusters throughout cyanobacteria, we reconstruct the convergent evolutionary history of HG structure, in which different clades produce the same HGs. We find that rudimentary HG biosynthetic machinery was already present in cyanobacteria before the emergence of heterocytes for functions unrelated to nitrogen fixation and identify HG analogs produced by specific and distantly related nonheterocytous cyanobacteria. These structurally less complex molecules represent precursors of HGs, suggesting that HGs arose after a genomic reorganization and expansion of ancestral biosynthetic machinery, enabling the rise of cyanobacterial heterocytes in an increasingly oxygenated atmosphere. Our results open a chapter in the potential use of diagenetic products of HGs and HG analogs as fossils for reconstructing the evolution of multicellularity and division of labor in cyanobacteria.